Preparation method of GelMA-BIL-PU hydrogel for human body tract fistula
Through the GelMA-BIL-PU hydrogel preparation method, spectral analysis and mechanical property testing were used to solve the problem of insufficient performance of hydrogel in the treatment of respiratory fistula, and achieve a higher production qualification rate and treatment effect.
Patent Information
- Application Number
- CN202410322762.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-20
- Publication Date
- 2025-09-30
AI Technical Summary
Existing hydrogels have poor mechanical properties, swelling properties, drug release properties and biodegradability when used to treat respiratory fistulas. The preparation process is complicated and its water absorption properties cannot be effectively tested, resulting in high production costs and low qualification rates.
The GelMA-BIL-PU hydrogel preparation method was adopted, and the separated mica, synthesized ionic liquid and GelMA structure were verified by 1H NMR and 13C NMR spectral analysis. Mechanical properties and rheological measurements, contact angle analysis and other steps were combined to ensure the performance testing and optimization of the hydrogel.
The mechanical stability, swelling rate control, drug release duration and biodegradation rate controllability of the hydrogel are improved, the production failure rate is reduced and the production qualification rate is improved.
Smart Images

Figure CN120718294A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogel preparation, and in particular to a method for preparing a GelMA-BIL-PU hydrogel for human cavity fistula. Background Art
[0002] Hydrogel is a type of extremely hydrophilic three-dimensional network structure gel that swells rapidly in water and can retain a large volume of water in this swollen state without dissolving. Hydrogel is needed in the treatment of respiratory fistulas, but the existing hydrogels have poor mechanical properties, swelling properties, drug release properties, and biological degradation properties, which reduces their effectiveness. Therefore, it is necessary to study new hydrogels. The preparation process of new hydrogels is relatively complicated, and their water absorption and other properties cannot be tested during the preparation process, which leads to an increase in their unqualified rate and increases the company's production costs. Summary of the Invention
[0003] The object of the present invention is to provide a method for preparing a GelMA-BIL-PU hydrogel for human cavity fistula, so as to solve the problems raised in the above background technology.
[0004] To achieve the above object, the present invention provides the following technical solution: a method for preparing a GelMA-BIL-PU hydrogel for human cavity fistula, comprising the following steps:
[0005] A, The structures of isolated mica, synthesized ionic liquid, and GelMA were verified by 1H NMR and 13C NMR spectroscopy in the presence of DMSO-d6 and D2O as solvents;
[0006] B. Add 10% by mass and volume of gelatin to 100 mL of deionized water, and stir the mixture in a 60°C oil bath until completely dissolved. Then, add 20% by mass and volume of methacrylic anhydride dropwise to the homogeneous gelatin solution.
[0007] C. Collect the pomegranate peel, dry and grind it, then reflux the extract powder twice with 50% ethanol for 3 hours to obtain a light yellow solution, which is then filtered, dried and concentrated. The residue is purified by high-mesh silica gel column chromatography using CHCl3:methanol as a solvent system to obtain a hydrogel;
[0008] D. Fourier transform infrared spectroscopy: using 500-4000cm -1 Infrared spectrometer with a resolution of 4 cm -1 , the scanning cycle was 120, and the functional group confirmation and structural changes of the prepared punicalagin, BIL, and gelatin-based bioadhesive hydrogel were recorded;
[0009] E, SEM scanning: surface morphology and pore size of the prepared GelMA and GelMA-based bioadhesive hydrogels were analyzed by SEM;
[0010] F. Water absorption study: GelMA, GelMA-BIL, and drug-loaded GelMA-BIL-PU hydrogels were used to study the swelling ratio;
[0011] G. Degradation study: The biodegradation of GelMA, GelMA BIL, and GelMA BIL-PU biohoneycomb hydrogels with dimensions of 10 mm wide and 5 mm high was studied by immersing them in DPBS containing 2.5 U / mL collagenase II at 37 °C with gentle shaking for time intervals of 4, 8, 12, 16, 20, and 28 days.
[0012] H. Release curve study: The prepared hydrogel samples GelMA BIL and GelMA BILPU with an average weight of 5 mg were freeze-dried and then immersed in 1 mL of PBS with a pH of 7.4 at 37°C to measure the release of PU and ionic liquid;
[0013] I. Contact Angle Analysis: To determine the hydrophilicity of GelMA, GelMA-BIL, and drug-loaded GelMA hydrogels, the water contact angles of the constructed hydrogels were analyzed;
[0014] J. Mechanical properties and rheological measurements: Mechanical testing of the prepared cylindrical hydrogel samples with a height of 10 mm and a diameter of 15 mm was examined using a universal testing machine. The samples were placed on the upper and lower fixtures and the inlet force was set to 0.01 N and the compression rate was 5 mm / min until the sample broke. In addition, using the above sample dimensions and appropriate compression fixtures, a 1000 N sensor and an inlet force of 0.01 N and a compression rate of 5 mm / min were used to detect the change in force with displacement during compression tests at ambient temperature.
[0015] K. Dissolution of PU in bioadhesive ionic liquid: The isolated PU was dissolved in a 10 mL round-bottom flask containing 1 g of choline bioadhesive ionic liquid, and the whole mixture was stirred until completely dissolved at ambient temperature;
[0016] L. Hydrogel preparation: To develop GelMA, GelMA-BIL, and PU-loaded BIL-GelMA hydrogels, 1 g of GelMA sponge was mixed with 10 mL of PBS solution and allowed to dissolve completely, and then 30 mg of lithium phenylphosphite was added to the GelMA solution in the dark.
[0017] Preferably, in step A, the fluctuation frequency of 1H NMR is 400 MHz, and the fluctuation frequency of 13C NMR is 100 MHz. In step B, the substitution reaction of methacryloyl group with the reactive -NH2 and -OH groups of gelatin is carried out in the dark for 3 hours to synthesize GelMA, and then the solution is freeze-dried at -80°C to produce a GelMA porous milky white sponge foam, and a choline binder ionic liquid is synthesized by a metathesis reaction. After washing with ethyl acetate, the BIL structure is verified by 1H NMR and 13C NMR spectroscopy, and stored at room temperature.
[0018] Preferably, in step C, the volume ratio of CHCl3:methanol is 9:1. In step E, the constructed hydrogel is first placed on a gold-plated aluminum stub, which is sputter-coated for 120 seconds after freeze-drying overnight to obtain a freeze-dried structure. The structure and surface morphology of the hydrogel sample are examined by 200-fold magnification at 20 kV high voltage.
[0019] Preferably, in step F, the hydrogel has a width of 10 mm and a height of 5 mm. The study method is as follows: a sample of the developed dried hydrogel is first weighed and then immediately immersed in DPBS at 37°C and pH 7.4 for 48 hours. Furthermore, the sample is extracted from the DPBS and the weight of the swollen hydrogel is calculated. The observed HSR is determined using the following formula: Where Wd is the dry hydrogel and Ws is the swollen hydrogel.
[0020] Preferably, in step G, at each interval, the freshly prepared collagenase solution is replaced, the undigested hydrogel sample is gently washed with DPBS, and its dry mass is estimated after drying at 50° C. under vacuum at appropriate time intervals. The observed RD is determined using the following formula: Where Wt is the final weight of the dry mass and W0 is the initial weight of the untreated hydrogel.
[0021] Preferably, in step H, release samples are collected every 1-7 days, and the release of PU and ionic liquid from the GelMA hydrogel is determined by measuring the UV absorption values at 372 nm and 226 nm, respectively, and then the release amounts of PU and BIL are calculated using the standard graphs of the two suspensions.
[0022] Preferably, in step I, a 1 cm×1 cm square of freeze-dried hydrogel is placed on a sample analyzer plate, and the water contact angle is evaluated using a drop shape analyzer DSA100. The water contact angle of each sample is recorded every 15 seconds, and the average water contact angle is calculated using Image J software.
[0023] Preferably, in step J, a rotational rheometer equipped with a parallel plate system is used to examine the rheological behavior of the sample. Before the experiment, the solution is placed in a stirrer at room temperature for two hours and tested in a sealed atmosphere at a temperature of 25°C. The effect of frequency on the storage modulus, loss modulus and viscosity is evaluated using a frequency sweep mode. The shear frequency range is 0.1-100 Hz, and the fixed strain is 1%. The thixotropic properties of the prepared samples are evaluated to determine their structural damage recovery ability. The contact test is performed by shearing the sample at 0.1s-1 for 50s, then shearing the sample at 1000s-1 for 20s, and then shearing the sample at 0.1s-1 for 50s. Before all measurements, the solution is pre-sheared at 1s-1 for 20s and the sample is allowed to equilibrate for 50s.
[0024] Preferably, in step K, the mass of PU is 5-100 mg, and the stirring process is extended for 1-24 hours based on the presence of PU particles or turbidity, and a uniform solution is fixed according to the addition of PU from low to high concentrations, and the required PU-BIL is used for hydrogel preparation.
[0025] Preferably, in step L, the phenyl group is 2,4,6-trimethylbenzoyl, the concentration of lithium phosphite is 0.05%, g / mL, and at the same time, 500 μL of the GelMA mixture and 500 μL of PU-BIL solution in which 5 mg of PU is dissolved are added to a 2 mL EP tube, and then exposed to ultraviolet light in the 405 nm band to produce a gel within 10 seconds. The prepared gel is then stored at room temperature, and its morphology is examined by SEM after freeze-drying.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The present invention can confirm the functional groups and structural changes of the hydrogel through Fourier transform infrared spectroscopy analysis, analyze the surface morphology and pore size of the hydrogel through SEM scanning, analyze the swelling rate of the hydrogel through water absorption research, detect the biodegradation rate of the hydrogel through degradation research, and analyze the water contact angle of the hydrogel through contact angle analysis. Therefore, while ensuring the overall performance of the hydrogel, the water absorption and other properties can also be detected, thereby improving the qualified rate of hydrogel production. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the GelMA structure of the present invention;
[0029] Figure 2 1H NMR spectrum of the GelMA structure of the present invention;
[0030] Figure 3 is a schematic diagram of the choline-based ionic liquid (BIL) of the present invention;
[0031] Figure 4 1H NMR spectrum of the BIL ionic liquid structure of the present invention;
[0032] Figure 5 This is the ESI-MS spectrum of the composite PU of the present invention;
[0033] Figure 6 1H NMR and 13CNMR spectra of the purified PU structure of the present invention;
[0034] Figure 7 SEM micrographs of GelMA, GelMA-BIL and GelMA-BIL-PU hydrogels of the present invention;
[0035] Figure 8 Figures 2 and 3 show (a) compression and (b) force-displacement studies of GelMA, GelMA-BIL, and GelMA-BIL-PU hydrogels of the present invention.
[0036] Figure 9 Graph showing the water contact angles of the GelMA, GelMA-BIL, and GelMA-BIL-PU hydrogels of the present invention;
[0037] Figure 10 Graph showing the swelling characteristics of GelMA, GelMA-BIL, and GelMA-BIL-PU hydrogels of the present invention;
[0038] Figure 11 Cumulative drug release profiles of BIL from GelMA-BIL and PU from GelMA BIL-PU hydrogels of the present invention;
[0039] Figure 12 Graph showing the biodegradation performance of GelMA, GelMA-BIL, and GelMA-BIL-PU hydrogels of the present invention;
[0040] Figure 13 Rheological experimental results of the present invention: (a) viscosity, (b) thixotropic behavior, (c) storage modulus (G'), and (d) loss modulus (G") of the synthesized BIL, GelMA, GelMA-BIL, and GelMA-BIL-PU samples. DETAILED DESCRIPTION
[0041] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making any creative efforts shall fall within the scope of protection of the present invention.
[0042] See also Figures 1-13 A method for preparing a GelMA-BIL-PU hydrogel for human cavity fistula comprises the following steps:
[0043] A, The structures of isolated mica, synthesized ionic liquid, and GelMA were verified by 1H NMR and 13C NMR spectroscopy in the presence of DMSO-d6 and D2O as solvents;
[0044] B. Add 10% by mass and volume of gelatin to 100 mL of deionized water, and stir the mixture in a 60°C oil bath until completely dissolved. Then, add 20% by mass and volume of methacrylic anhydride dropwise to the homogeneous gelatin solution.
[0045] C. Collect the pomegranate peel, dry and grind it, then reflux the extract powder twice with 50% ethanol for 3 hours to obtain a light yellow solution, which is then filtered, dried and concentrated. The residue is purified by high-mesh silica gel column chromatography using CHCl3:methanol as a solvent system to obtain a hydrogel;
[0046] D. Fourier transform infrared spectroscopy: using 500-4000cm -1 Infrared spectrometer with a resolution of 4 cm -1 , the scanning cycle was 120, and the functional group confirmation and structural changes of the prepared punicalagin, BIL, and gelatin-based bioadhesive hydrogel were recorded;
[0047] E, SEM (electron microscopy) scanning: surface morphology and pore size of the prepared GelMA and GelMA-based bioadhesive hydrogels were analyzed by SEM;
[0048] F. Water absorption study: GelMA, GelMA-BIL, and drug-loaded GelMA-BIL-PU hydrogels were used to study the swelling ratio;
[0049] G. Degradation study: The biodegradation of GelMA, GelMA BIL, and GelMA BIL-PU biohoneycomb hydrogels with dimensions of 10 mm wide and 5 mm high was studied by immersing them in DPBS containing 2.5 U / mL collagenase II at 37 °C with gentle shaking for time intervals of 4, 8, 12, 16, 20, and 28 days.
[0050] H. Release curve study: The prepared hydrogel samples GelMA BIL and GelMA BILPU with an average weight of 5 mg were freeze-dried and then immersed in 1 mL of PBS with a pH of 7.4 at 37°C to measure the release of PU and ionic liquid;
[0051] I. Contact Angle Analysis: To determine the hydrophilicity of GelMA, GelMA-BIL, and drug-loaded GelMA hydrogels, the water contact angles of the constructed hydrogels were analyzed;
[0052] J. Mechanical properties and rheological measurements: Mechanical testing of the prepared cylindrical hydrogel samples with a height of 10 mm and a diameter of 15 mm was examined using a universal testing machine. The samples were placed on the upper and lower fixtures and the inlet force was set to 0.01 N and the compression rate was 5 mm / min until the sample broke. In addition, using the above sample dimensions and appropriate compression fixtures, a 1000 N sensor and an inlet force of 0.01 N and a compression rate of 5 mm / min were used to detect the change in force with displacement during compression tests at ambient temperature.
[0053] K. Dissolution of PU in bioadhesive ionic liquid: The isolated PU was dissolved in a 10 mL round-bottom flask containing 1 g of choline bioadhesive ionic liquid, and the whole mixture was stirred until completely dissolved at ambient temperature;
[0054] L. Hydrogel preparation: To develop GelMA, GelMA-BIL, and PU-loaded BIL-GelMA hydrogels, 1 g of GelMA sponge was mixed with 10 mL of PBS solution and allowed to dissolve completely, and then 30 mg of lithium phenylphosphite was added to the GelMA solution in the dark.
[0055] In step A, the fluctuation frequency of 1H NMR is 400 MHz, and the fluctuation frequency of 13C NMR is 100 MHz. In step B, the substitution reaction of methacryloyl group with the reactive -NH2 and -OH groups of gelatin is carried out in the dark for 3 hours to synthesize GelMA (gelatin methacryloyl group), and then the solution is freeze-dried at -80°C to produce GelMA porous milky white sponge foam. A choline binder ionic liquid is synthesized by a double decomposition reaction. After washing with ethyl acetate, the structure of the obtained BIL (choline binder ionic liquid) is verified by 1H NMR and 13C NMR spectroscopy and stored at room temperature.
[0056] In step C, the volume ratio of CHCl3:methanol was 9:1. In step E, the constructed hydrogel was first placed on a gold-coated aluminum stub, which was sputter-coated for 120 seconds after freeze-drying overnight to obtain the freeze-dried structure. The structure and surface morphology of the hydrogel sample were examined by 200-fold magnification under a high voltage of 20 kV.
[0057] In step F, the hydrogel had a width of 10 mm and a height of 5 mm. The study method was as follows: the developed dried hydrogel sample was first weighed and then immediately immersed in DPBS (Dubric phosphate buffered saline) at 37°C and pH 7.4 for 48 hours. In addition, the sample was extracted from the DPBS and the weight of the swollen hydrogel was calculated. The observed HSR (hydrogel swelling ratio) was determined using the following formula: Where Wd is the dry hydrogel and Ws is the swollen hydrogel.
[0058] In step G, at each interval, the collagenase solution was replaced with freshly prepared solution, and the undigested hydrogel samples were gently washed with DPBS and dried at 50°C under vacuum at appropriate time intervals to estimate their dry mass. The observed RD (degradation rate) was determined using the following formula: Where Wt is the final weight of the dry mass and W0 is the initial weight of the untreated hydrogel.
[0059] In step H, release samples were collected every 1–7 days to determine the release of PU and ionic liquid from the GelMA hydrogel by measuring the UV absorbance at 372 nm and 226 nm, respectively. The release amounts of PU and BIL were then calculated using the respective standard graphs of the two suspensions.
[0060] In step I, a 1 cm × 1 cm square of freeze-dried hydrogel was placed on the sample analyzer plate and the water contact angle (WCA) was evaluated using a drop shape analyzer DSA100. The water contact angle of each sample was recorded every 15 seconds, and the average water contact angle was calculated using ImageJ software.
[0061] In step J, a rotational rheometer equipped with a parallel plate system is used to examine the rheological behavior of the sample. Before the experiment, the solution is placed in a stirrer at room temperature for two hours and tested in a sealed atmosphere at a temperature of 25°C. The effect of frequency on the storage modulus, loss modulus and viscosity is evaluated using a frequency sweep mode with a shear frequency range of 0.1-100 Hz and a fixed strain of 1%. The thixotropic properties of the prepared samples are evaluated to determine their structural damage recovery ability. The contact test is performed by shearing the sample at 0.1s-1 for 50s, then shearing the sample at 1000s-1 for 20s, and then shearing the sample at 0.1s-1 for 50s. Before all measurements, the solution is pre-sheared at 1s-1 for 20s and the sample is allowed to equilibrate for 50s.
[0062] In step K, the mass of PU was 5–100 mg, and the stirring process was extended for 1–24 h based on the presence of PU particles or turbidity, and a uniform solution was fixed according to the low to high concentration of PU addition, and the desired PU-BIL was used for hydrogel preparation.
[0063] In step L, the phenyl group was 2,4,6-trimethylbenzoyl, and the concentration of lithium phosphite was 0.05% g / mL. At the same time, 500 μL of the GelMA mixture and 500 μL of PU-BIL solution containing 5 mg of PU were added to a 2 mL EP tube and then exposed to UV light in the 405 nm band to produce a gel within 10 seconds. The prepared gel was then stored at room temperature, and its morphology was examined by SEM after freeze-drying.
[0064] It also includes the experimental results of GelMA-BIL-PU hydrogel preparation and phenotypic analysis, which include GelMA-BIL-PU hydrogel structure analysis and purification, mechanical properties of hydrogel, contact angle, swelling experiment, drug release experiment, biological degradation experiment and rheology experiment.
[0065] GelMA-BIL-PU hydrogel structure analysis and purification:
[0066] The structure of the synthesized gelatin methacryloyl (GelMA) was confirmed by 1H NMR analysis. The gelatin-methacryloyl group contained acrylic acid protons in the range of δ5.4 and δ5.6 ppm, and methyl protons were also shown at δ1.8 ppm, which confirmed that the methacrylic acid reaction in GelMA was indeed effective. To verify the reduction of the amino group concentration in GelMA, a decrease in the intensity peak was observed in the range between δ2.9 and δ3 ppm. In addition, Figure 1-2 In the present study, phenylalanine protons were detected from δ7.0–7.5 ppm. Therefore, the regression peak of the methacrylic acid functional group at δ2.9 ppm was used to determine the level of gelatin-methacryloyl substitution. The conversion rate was about 80% or more. The chemical composition of the synthesized choline bioadhesive ionic liquid was determined by proton and carbon chemical shifts. By comparing the measured chemical shifts of the reactant 3-(3,4-dihydroxyphenyl)propionic acid with the 1H NMR data of the final ionic liquid structure, it was confirmed that the synthesized choline propionate bioadhesive containing three aromatic protons showed a doublet at δ6.55 and 6.38 ppm. The quaternary ammonium containing 9 methyl protons was depicted as a singlet at δ3.09 ppm, which was determined to be the confirmation of the composition of the 3,4-dihydroxyphenylpropionic acid choline structure ( Figure 3-4), while, choline containing two methylene protons appeared in δ3.8-3.2ppm, it is noteworthy that in the spectrum of choline propionate, the -COOH (broad singlet at δ12.05ppm) supported by 3-(3,4-dihydroxyphenyl)propionic acid disappeared, which confirmed the formation of the ionic liquid structure, and in the 13C NMR spectrum of choline ionic liquid, the peaks of carbonyl carbon ((-C=O)) and –CH3 and –CH2 carbon at δ177.1ppm were in the range of δ67.5-32.1ppm, therefore, the confirmation of the synthesized ionic liquid structure was confirmed by observing the chemical shifts of 1H and 13C NMR spectroscopy analysis, and by 1H, 13C The structure of the purified punicalagin (PU) was confirmed by NMR and mass spectrometry analysis. In the PU structure, four aromatic protons classified as C-23, C-46, C-18, and C-9 were observed at δ 6.7-66.4 ppm, while signals of positions C-1 to C-5 containing five protons were found at δ 1.9-3.1 ppm, and position C-6 with two -CH2 protons was observed at δ 4.6-4.7 ppm. The remaining -OH protons were detected in the appropriate region of the NMR spectrum. In the 13C spectrum, the four carbonyl (C-7, C-20, C-21, and C-48) carbons in the PU structure were demonstrated from δ170.39-166.42 ppm. The signal of the chiral carbon (C-1) was shown at δ100.6 ppm. Other carbons were observed at appropriate positions, while the methylene carbon peak containing C-6 was around δ19.4 ppm. In addition, the mass spectrum showed that the actual mass of the observed structure was approximately m / z = 1107 [m++Na] ion. Therefore, the results of the above NMR and mass spectrometry studies confirmed the correct structure of pure PU, as shown in Figure 2. Figure 5-6 As shown in Figure 3, the structural morphology of GelMA hydrogels and the morphological changes of GelMA-BIL and GelMA-BIL-PU hydrogels injected with BIL and PU were examined by scanning electron microscopy (SEM). Compared with the surface of hydrogels incorporating BIL and PU, the surface morphology of GelMA hydrogels was observed to be more microporous, which indicates that the presence of equal amounts of photoinitiators stimulated the macrostructural and bioadhesive BIL chemical bond communication of PU, thereby forming a more compact cross-linked structure. Sufficient physicochemical connections were built in between BIL, PU bioactive agents and gelatin-methacrylate polymer network, as shown in Figure 3. Figure 7 As shown, the microstructure in GelMA BIL and GelMA BIL PU compositions is low, and data from scanning electron microscopy (SEM) indicate that the bioadhesive properties of BIL and multifunctional PU can directly affect the pore density of the hydrogel, which is beneficial to improve the mechanical stability and controllable degradability without affecting the supply of biological properties for delivering the desired cell behavior to repair cartilage tissue / organs;
[0067] Mechanical properties of hydrogels:
[0068] The mechanical properties of hydrogel implants are crucial for their application in damaged bones and flexible connective tissue remodeling. The long-term delivery and therapeutic effects of hydrogel-compressed bioactive substances can only be directly related to the inherent stability and structure of the implant. Therefore, the prepared GelMA, GelMA-BIL and GelMA-BIL-PU hydrogel samples were subjected to compression and force-displacement studies and evaluations. The compressive strength and strain of GelMA hydrogel reached 0.1492MPa and 64.85%, respectively. At the same time, compared with GelMA, GelMA-BIL and GelMA-BIL-PU hydrogels showed significantly higher compressive strength and strain. The stresses of the hydrogels were about 0.2954 MPa and 0.4229 MPa, respectively, and the strains were 71.92% and 67.55%, respectively. Due to the strong intramolecular connections and electrostatic attraction, hydrogen bonding and hydrophobic interactions in the molecular geometry of the GelMA-BIL-PU spatial arrangement and polymer chains, the stability and ability to withstand stresses of the hydrogels were higher than those of GelMA-BIL. The strains obtained showed that the stresses of the GelMA-BIL-PU hydrogels were slightly lower than those of the GelM-BIL group, which may be attributed to the presence of more hydroxyl groups in the PU structure, which may lead to the formation of highly tight binding and stable alliances in the molecular network. It is worth noting that, as shown in Figure 2, the stresses of the hydrogels were about 0.2954 MPa and 0.4229 MPa, respectively, and the strains were 71.92% and 67.55%, respectively. Due to the strong intramolecular connections and electrostatic attraction, hydrogen bonding and hydrophobic interactions in the molecular geometry of the GelMA-BIL-PU spatial arrangement and polymer chains, the stability and ability to withstand stresses of the hydrogels were higher than those of the GelMA-BIL group. The strains obtained showed that the stresses of the GelMA-BIL-PU hydrogels were slightly lower than those of the GelM-BIL group, which may be attributed to the presence of more hydroxyl groups in the PU structure, which may lead to the formation of highly tight binding and stable alliances in the molecular network. It is worth noting that, as shown in Figure 2, the stresses of the hydrogels were about 0.2954 MPa and 0.4229 MPa, respectively, and the strains Figure 9 As shown, the viscosity of the obtained GelMA-BIL-PU is higher than that of GelMA-BIL. Although the GelMA-BIL-PU group shows slight degradation in strain, it exhibits excellent sustained release and slow degradation due to the strong cross-linked structure formed by intramolecular or intermolecular bonding, which helps to improve biocompatibility and accelerate the healing of damaged tissue networks. In addition, the force-displacement effectiveness of the hydrogel depends on the toughness and compactness of the structure as the penetration force increases. Thus, on pure GelMA, deformation occurred within a range of 7 mm when an applied force of 9 N was applied, and complete rupture occurred within a range of 8.6 mm when a force of 8.75 N was applied. When bioactive components were combined with pure GelMA to develop GelMA-BIL and GelMA-BIL PU, durability of the hydrogel and greater binding force were noted. Thus, at an applied force of 18.8 N, the deformation range of the GelMA-BIL hydrogel was only 6.9 mm. Compared with GelMA-BIL and pure GelMA hydrogels, the deformation amplitude of the GelMA-BIL-PU hydrogel showed a smaller displacement (deformation of 6.1 mm) at a higher applied force (N = 26.1), as shown in Figure 3. Figure 8As shown in (b), the polymer chain backbone with functional groups and the integrated bioactive molecules containing negatively charged atoms and positively and negatively charged chemical bonds can play a key role in the intra- and intermolecular affinity to improve the rigidity and stability of the hydrogel in the structure. Therefore, compared with GelMA-BIL and GelMA hydrogels, the GelMA-BIL-PU hydrogel polymer network has significantly smaller deformation and breakability, which is due to the amount of charged atoms and the higher concentration of electronegative atoms;
[0069] (3) Contact angle:
[0070] The surface roughness and hydrophilicity range of the constructed hydrogels were analyzed by water contact angle measurements. The contact angle test results of the hydrogels GelMA, GelMA-BIL, and GelMA-BIL-PU show how the effectiveness of intermolecular forces evolves once water is attracted to the sample surface. When droplets accumulate on the surface of a hydrogel made of hydrophilic components, the surface tension of the hydrogel may decrease due to the porosity of the hydrogel, thereby reducing the contact angle. As a result, the contact angle achieved by the GelMA group within 10 seconds was approximately 39.822.0°, while the BIL-incorporated GelMA-BIL hydrogel group and the GelMA-BIL-PU group displaced 45.50 ± 3.5° and 49.50 ± 3.0°, respectively, at 10 seconds. 4.4°. It is worth noting that the group made of viscous materials showed an increased contact angle due to the low porosity in the structure. The hydrogel formation can promote cell-to-cell communication and cell expansion due to its permeability and porous structure. Although the GelMA-BIL and GelMA-BIL-PU composites have more amide and hydroxyl imaginary groups than pure GelMA, GelMA-BIL and GelMA-BIL-PU show larger contact angles than GelMA. Figure 9 Only minor changes between them are shown, indicating that the adhesive properties may initially reduce the surface tension of the adhered hydrogel surface, thus, after 10 seconds, the contact angle of GelMA BIL PU was observed to be 49.50 4.4°;
[0071] (4) Expansion test:
[0072] Designing hydrogels with three-dimensional intermolecular networks can give them an inherent hydrophilic advantage, allowing them to swell in aqueous environments without dissolving, which enhances the hydrogel's strong hydrophilicity, permeability, and the ability to develop microenvironments for applications such as biomedical implants or sustained drug delivery. Injecting bioactive ingredients into polymer hydrogel networks plays a vital role in structural rigidity, swelling capacity for absorbing or releasing nutrients, therapeutic agents, and eliminating metabolic waste during the healing process of damaged tissues. Therefore, Figure 10The swelling behavior rates of GelMA, GelMA-BIL and GelMA-BIL-PU at different time intervals were indicated. In pure GelMA hydrogel, a strong swelling trend of 91% was shown after one hour. When the time interval was extended to 25 hours, the water absorption capacity also increased. After 25 hours of observation, the swelling degree of the GelMA group was significantly higher than that of the GelMA group. Figure 10 The swelling rates of GelMA-BIL and GelMA-BIL-PU groups were more than 300% higher than those of GelMA-BIL and GelMA-BIL-PU groups shown. Recently, major efforts have been made to encapsulate drugs in biomaterials to stop excretion or delivery in a short time without achieving the desired results. The swelling rates of GelMA-BIL and GelMA-BIL-PU measured after 25 hours were 259% and 210%, respectively. The test verified the ability to absorb water under control, as shown in Figure 2. Figure 10 As shown, the water absorption capacity of the hydrogel should be enhanced by adding water-soluble components to the large number of hydrophilic polymers used in its synthesis. In contrast, when the hydrophilic bioadhesive ionic liquid was introduced into the hydrogel GelMA-BIL, the water absorption of the hydrogel decreased. This is because the GelMA hydrogel is more porous than the GelMA Bili. It is worth noting that the GelMA-BIL-PU hydrogel incorporated with bioactive PU drugs showed a lower swelling rate than the GelMA Bili hydrogel; the reason for the weaker water absorption capacity of the GelMA-BIL-PU hydrogel may be related to the lower capillary force and the stable cross-linking between the polymer and the hydroxyl-containing PU bioactive molecules. The results indicate that the bioadhesive combination will effectively control the swelling behavior. The use of appropriate therapeutic agents will help maintain stability throughout the repair process, especially in bone and cartilage regeneration applications ( Figure 10 );
[0073] (5) Drug release experiment:
[0074] Hydrogel-based drug delivery technologies are currently used in clinical settings and can exploit therapeutic benefits associated with drug delivery. Ideal amounts of drugs can be embedded in hydrogels for targeted sustained-release applications due to their unique physicochemical properties and high biocompatibility. Gelatin-based hydrogels incorporated with bioactive substances may be able to construct intermolecular bonding configurations with hydrophilic macromonomers, which can enable regulated drug delivery to desired organs or tissues. Puncaragin (PU) and bioadhesive choline ionic liquid (BIL) were released from GelMA-BIL-PU and GelMA-BIL hydrogels using PBS (pH 7.4) and monitored for up to 7 days. Figure 11The results showed that after one day of incubation in PBS, BIL released about 34% and PU released 14%. The release of bioactive BIL and PU also increased with the extension of incubation time; it reached about 57% on the fifth day. Importantly, the release of BIL from GelMA-BIL became saturated after the fifth day of observation, while the release of PU from GelMA-BIL-PU showed 68% delivery on the seventh day of incubation. The results showed that compared with PU composed of GelMA-BIL-PU hydrogel, the high hydrophilicity of GelMA-BIL easily participated in the diffusion and swelling process through hydrolysis. Therefore, GelMA-BIL-PU hydrogel showed longer sustained release than GelMA-BIL. Compared with pure GelMA hydrogel, the opposite charge Internal electrostatic attraction between GelMA-BIL and GelMA-BIL contributes to the creation of a complex matrix structure and improved stability due to the presence of an ionic phase within the GelMA-BIL structure. Furthermore, the presence of charged moieties and more electronegative atoms bound to GelMA-BIL-PU compared to GelMA-BIL can generate favorable forces and affinities within and between the molecular geometry of the polymer chains, enhancing their electrical resistance. Consequently, the GelMA-BIL-PU system exhibited superior dye delivery results from the first to seventh day of culture. The GelMA-BIL-PU system can more effectively provide stability through controlled release to enhance the biological response to reconstruct the full function of musculoskeletal tissue.
[0075] (6) Biological degradation experiment:
[0076] The degradation ability of hydrogels is an important aspect that affects the healing of damaged tissues. The appropriate biodegradation rate occurring at the right time is crucial for replenishing newly synthesized ECM and tissue. Here, hydrogel samples of GelMA, bioadhesive GelMA-BIL, and GelMA-BIL-PU were used for enzymatic degradation studies at intervals of 4 to 28 days. Figure 12As shown, GelMA allows for greater absorption of collagenase into the hydrogel structure due to its increased porosity, which accelerates the disassembly of the complex polymer structure and disrupts important chemical connections. As a result, the disassembly rate of GelMA hydrogels rose by approximately 43% to 97% after 5 to 25 days. The degradation rates of GelMA-BIL and GelMA-BIL-PU hydrogels were approximately 35%, 23% after 5 days of study, and 81% and 67% after 25 days of observation. When GelMA-BIL-PU was compared with the GelMA-BIL and GelMA groups in vitro, long-term degradation was demonstrated. Using three different composition types of GelMA, BIL, and PU, targeted GelMA-BIL-PU hydrogels were made possible by the use of a photoinitiator that causes free radical chain polymerization upon exposure to light. Therefore, each chemical The chemical components can easily combine them with intermolecular interactions or affinities of oppositely charged atoms or functional groups to produce interconnected, compact hydrogel structures. In this case, the presence of positive ions and atoms from catechol groups, including BIL with choline, can lead to the formation of hydrogen bonds between the peptide backbones of the GelMA polymer. The development of tighter instant hydrogel adhesion in the structure can be supported by PU containing a large number of aromatic and hydroxyl groups, as it can induce π-π / cation-π interactions and condense with the aromatic and charged BIL structure. The above-mentioned chemical bonds may be responsible for the combined polyphenol structure of catechol groups and charged parts, which can enhance the durability and adhesion of hydrogels made of GelMA. Therefore, GelMA-BIL-PU exhibits controllable degradation and is suitable for stem cell loading and scaffolding.
[0077] (7) Rheological experiments:
[0078] The rheological properties of the prepared BIL, GelMA, GelMA-BIL, and GelMA-BIL-PU gels were examined to determine the physicochemical changes (flow behavior and viscoelastic properties) that occur when the gel materials are mixed with various bioactive compounds or drugs. A rotational rheometer equipped with a parallel plate system was used to examine the rheological behavior of the samples, e.g. Figure 13 As shown in the results, under applied shear (shear rate of 1-1000s-1), the shear thinning behavior of each gel formed changed, and the fluid viscosity was found to decrease with increasing shear rate. A noteworthy finding was that the viscosity level of the gel changed as one component was added to the other, with the viscosity of the GelMA-BIL-PU group being higher (over 500Pa) than the other groups, as shown in the results of the present study. Figure 13As shown, the enhanced gel viscosity in the combined GelMA-BIL-PU structure demonstrated that the fixed concentration of GelMA gel was not affected by the bioactive molecules (PU) and bioadhesive materials (BIL). The charged adhesive ionic liquid and high molecular weight polyphenol present in the polymer matrix could thus produce ionic gels, which could provide better defined properties for GelMA-BIL-PU gels. The time-dependent thixotropic behavior of the synthesized gels at 25°C was studied to evaluate their reversibility potential. Figure 13 All gels showed that they quickly recovered to their normal viscosity after high shear rate, with no hysteresis within 20 seconds. This indicates that the gels were able to maintain their shape fidelity under high shear conditions. Due to the combined structure of BIL and PU in the GelMA-BIL-PU group, the molecular arrangement may have changed. Therefore, the observed results clearly indicate that the GelMA-BIL-PU gel structure containing ionic and covalently bonded atoms may be the main factor in the formation of a well-organized molecular arrangement, which takes time to recover to its original state under high shear. When BIL and PU are combined in the GelMA-BIL-PU structure, we found a moderate difference in recovery, which may be caused by increased electrostatic attraction within the gel structure. The observations indicate that the ability of each gel to maintain its shape is not particularly remarkable. However, the zwitterionic form of BIL is significantly different from that of the GelMA-based gels. The combination of aromatic polyphenols in the BIL-PU structure can exhibit enhanced mechanical prosperity, which will be suitable for tracheal defect repair. In addition, the viscoelastic properties of the hydrogels were investigated using frequency sweep tests in the range of 0.1–100 Hz. The storage modulus (G') values of the hydrogels were higher compared to the loss modulus (G") obtained. The loss modulus represents the intrinsic elastic structure of the hydrogel. However, we did not notice much significant change in the storage modulus between the GelMA and BIL-encapsulated hydrogels, while BIL and PU had no negative impact, but instead provided evidence that favored the improvement of important viscoelastic properties. Therefore, by increasing the applied frequency range at a constant temperature, the viscoelastic (G' and G") properties were enhanced. The accelerated elastic and viscous effects mentioned above help maintain the structural stability and flexibility of the gel, making it a suitable building block for the production of injectable hydrogels for tissue engineering applications.
[0079] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a GelMA-BIL-PU hydrogel for human cavity fistula, characterized in that: The following steps are involved: A, The structures of isolated mica, synthesized ionic liquid, and GelMA were verified by 1H NMR and 13C NMR spectroscopy in the presence of DMSO-d6 and D2O as solvents; B. Add 10% by mass and volume of gelatin to 100 mL of deionized water, and stir the mixture in a 60°C oil bath until completely dissolved. Then, add 20% by mass and volume of methacrylic anhydride dropwise to the homogeneous gelatin solution. C. Collect the pomegranate peel, dry and grind it, then reflux the extract powder twice with 50% ethanol for 3 hours to obtain a light yellow solution, which is then filtered, dried and concentrated. The residue is purified by high-mesh silica gel column chromatography using CHCl3:methanol as a solvent system to obtain a hydrogel; D. Fourier transform infrared spectroscopy: using 500-4000cm -1 Infrared spectrometer with a resolution of 4 cm -1 , the scanning cycle was 120, and the functional group confirmation and structural changes of the prepared punicalagin, BIL, and gelatin-based bioadhesive hydrogel were recorded; E, SEM scanning: surface morphology and pore size of the prepared GelMA and GelMA-based bioadhesive hydrogels were analyzed by SEM; F. Water absorption study: GelMA, GelMA-BIL, and drug-loaded GelMA-BIL-PU hydrogels were used to study the swelling ratio; G. Degradation study: The biodegradation of GelMA, GelMA BIL, and GelMA BIL-PU biohoneycomb hydrogels with dimensions of 10 mm wide and 5 mm high was studied by immersing them in DPBS containing 2.5 U / mL collagenase II at 37 °C with gentle shaking for time intervals of 4, 8, 12, 16, 20, and 28 days. H. Release curve study: The prepared hydrogel samples GelMA BIL and GelMA BIL PU with an average weight of 5 mg were freeze-dried and then immersed in 1 mL of PBS with a pH of 7.4 at 37°C to measure the release of PU and ionic liquid; I. Contact Angle Analysis: To determine the hydrophilicity of GelMA, GelMA-BIL, and drug-loaded GelMA hydrogels, the water contact angles of the constructed hydrogels were analyzed; J. Mechanical properties and rheological measurements: Mechanical testing of the prepared cylindrical hydrogel samples with a height of 10 mm and a diameter of 15 mm was examined using a universal testing machine. The samples were placed on the upper and lower fixtures and the inlet force was set to 0.01 N and the compression rate was 5 mm / min until the sample broke. In addition, using the above sample dimensions and appropriate compression fixtures, a 1000 N sensor and an inlet force of 0.01 N and a compression rate of 5 mm / min were used to detect the change in force with displacement during compression tests at ambient temperature. K. Dissolution of PU in bioadhesive ionic liquid: The isolated PU was dissolved in a 10 mL round-bottom flask containing 1 g of choline bioadhesive ionic liquid, and the whole mixture was stirred until completely dissolved at ambient temperature; L. Hydrogel preparation: To develop GelMA, GelMA-BIL, and PU-loaded BIL-GelMA hydrogels, 1 g of GelMA sponge was mixed with 10 mL of PBS solution and allowed to dissolve completely, and then 30 mg of lithium phenylphosphite was added to the GelMA solution in the dark.
2. The method for preparing a GelMA-BIL-PU hydrogel for human cavity fistula according to claim 1, wherein: In step A, the 1H NMR fluctuation frequency is 400 MHz, and the 13C NMR fluctuation frequency is 100 MHz. In step B, a substitution reaction of methacryloyl groups with reactive -NH2 and -OH groups of gelatin is carried out in the dark for 3 hours to synthesize GelMA, and then the solution is freeze-dried at -80°C to produce a GelMA porous milky white sponge-like foam. A choline binder ionic liquid is synthesized by a metathesis reaction, and after washing with ethyl acetate, the BIL structure is verified by 1H NMR and 13C NMR spectroscopy, and the foam is stored at room temperature.
3. The method for preparing a GelMA-BIL-PU hydrogel for human cavity fistula according to claim 1, characterized in that: In step C, the volume ratio of CHCl3:methanol is 9:
1. In step E, the constructed hydrogel is first placed on a gold-plated aluminum stub, which is then sputter-coated for 120 seconds after freeze-drying overnight to obtain a freeze-dried structure. The structure and surface morphology of the hydrogel sample are examined by 200-fold magnification under a high voltage of 20 kV.
4. The method for preparing a GelMA-BIL-PU hydrogel for human cavity fistula according to claim 1, characterized in that: In step F, the hydrogel had a width of 10 mm and a height of 5 mm. The study method was as follows: the developed dried hydrogel sample was first weighed and then immediately immersed in DPBS at 37°C and pH 7.4 for 48 hours. In addition, the sample was extracted from the DPBS and the weight of the swollen hydrogel was calculated. The observed HSR was determined using the following formula: Where Wd is the dry hydrogel and Ws is the swollen hydrogel.
5. The method for preparing a GelMA-BIL-PU hydrogel for human cavity fistula according to claim 1, characterized in that: In step G, freshly prepared collagenase solution was replaced at each interval, and the undigested hydrogel sample was gently washed with DPBS and dried at 50°C under vacuum at appropriate time intervals to estimate its dry mass. The observed RD was determined using the following formula: Where Wt is the final weight of the dry mass and W0 is the initial weight of the untreated hydrogel.
6. The method for preparing a GelMA-BIL-PU hydrogel for human cavity fistula according to claim 1, characterized in that: In step H, release samples were collected every 1-7 days, and the release of PU and ionic liquid from the GelMA hydrogel was determined by measuring the UV absorption values at 372 nm and 226 nm, respectively. The release amounts of PU and BIL were then calculated using the standard graphs of the two suspensions.
7. The method for preparing a GelMA-BIL-PU hydrogel for human cavity fistula according to claim 1, characterized in that: In step I, a 1 cm×1 cm square of freeze-dried hydrogel was placed on a sample analyzer plate, and the water contact angle was evaluated using a drop shape analyzer DSA100. The water contact angle of each sample was recorded every 15 seconds, and the average water contact angle was calculated using ImageJ software.
8. The method for preparing a GelMA-BIL-PU hydrogel for human cavity fistula according to claim 1, characterized in that: In step J, a rotational rheometer equipped with a parallel plate system is used to examine the rheological behavior of the sample. Prior to the experiment, the solution is placed in a stirrer at room temperature for two hours and tested in a sealed atmosphere at a temperature of 25°C. The effect of frequency on the storage modulus, loss modulus and viscosity is evaluated using a frequency sweep mode. The shear frequency range is 0.1-100 Hz, and the fixed strain is 1%. The thixotropic properties of the prepared samples are evaluated to determine their structural damage recovery ability. The contact test is performed by shearing the sample at 0.1s-1 for 50s, then shearing the sample at 1000s-1 for 20s, and then shearing the sample at 0.1s-1 for 50s. Before all measurements, the solution is pre-sheared at 1s-1 for 20s and the sample is allowed to equilibrate for 50s.
9. The method for preparing the GelMA-BIL-PU hydrogel for human cavity fistula according to claim 1, characterized in that: In step K, the mass of PU is 5-100 mg, and the stirring process is extended for 1-24 hours based on the presence of PU particles or turbidity, and a uniform solution is fixed according to the low to high concentration of PU addition, and the required PU-BIL is used for hydrogel preparation.
10. The method for preparing the GelMA-BIL-PU hydrogel for human cavity fistula according to claim 1, characterized in that: In the step L, the phenyl group is 2,4,6-trimethylbenzoyl, and the concentration of lithium phosphite is 0.05%, g / mL. At the same time, 500 μL of the GelMA mixture and 500 μL of PU-BIL solution in which 5 mg of PU is dissolved are added to a 2 mL EP tube, and then exposed to ultraviolet light in the 405 nm band to produce a gel within 10 seconds. The prepared gel is then stored at room temperature, and its morphology is examined by SEM after freeze-drying.